Galicia e os descubridores oceánicos a través de Amancio Landín - Blanco Ramos, Carmen (Madrygal. Revista de Estudios Gallegos, 2008)
This article tries to make Amancio Landín known to the readers. He was a man with a passion for oceanic discoveries, and with an especial interest in the vindication of Galician sailors.
Keywords: Discoverers galician; Vindication galeguidade